2022
DOI: 10.3389/fcvm.2022.878211
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study to Detect Immune Checkpoint Inhibitors Associated With Myocarditis Among Patients Treated for Lung Cancer

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) are widely used in lung cancer management. However, myocarditis, which is a rare, yet potentially severe adverse-related event associated with ICIs, could be under-reported.ObjectivesThis study is aimed to prospectively evaluate the cumulative incidence rate of myocarditis, through systematic screening, among patients receiving ICIs for lung cancer.MethodsAll patients who received the first administration of ICIs for non-small cell (NSCLC) and small cell lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Systematic screening was also performed in a prospective, single-center study by Faubry et al which included 99 patients [55]. The main objective was to determine the incidence of myocarditis and other CV irAEs in ICI-treated patients with stage IIIB-IV lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic screening was also performed in a prospective, single-center study by Faubry et al which included 99 patients [55]. The main objective was to determine the incidence of myocarditis and other CV irAEs in ICI-treated patients with stage IIIB-IV lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the OSs, our results show that ICI use was not associated with increased risk of myocarditis ( P =0.09) or pericardial disease ( P =0.19, Figure 6 , 14 , 17 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ). However, the use of combination ICIs was associated with higher risk of myocarditis (OR, 3.07 [95% CI, =1.28–7.39], P <0.02) but not pericardial disease (OR, 4.13 [95% CI, 0.19–89.86], P <0.67) compared with single ICI therapy in OSs.…”
Section: Resultsmentioning
confidence: 70%
“… Forest plot of included OSs, separated based on therapy comparisons for myocarditis 14 , 17 , 53 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ( A ) and pericardial disease 17 , 53 , 54 , 55 , 56 ( B ). The squares and horizontal lines correspond to the study‐specific ORs and 95% CIs.…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding, we were taken aback by the very low incidence of ICI-related MACE in this pooled analysis of trials (0.6% of patients treated), with an incidence of myocarditis as low as 0.26%, whereas myocarditis may occur in more than 1% of patients 3 with a recent report of a 3% incidence through a prospective study in patients with lung cancer. 4 Additionally, a recent retrospective study reported an incidence of 10.3% of nonmyocarditis MACEs (acute coronary syndrome, heart failure, stroke, and transient ischemic attack) through a median follow-up of 13 months. 5 This underestimation of ICI-related MACE found in the NCI trials database may stem from numerous facts.…”
mentioning
confidence: 99%